EKRANISASI NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KE DALAM FILM (PENDEKATAN STRUKTURAL) - Musyafir, Musyafir; Lembah, Gazali; Kangiden, Nurhaya (BAHASANTODEA, 2017)
The problem of this research is novel ecranization of Tenggelamnya Kapal Van Der Wijck to the movie that include varying shrink, addition and changes. This research aims to describe the novel ecranization of Tenggelamnya Kapal Van Der Wijck by Hamka into the movie of Tenggelamnya Kapal Van Der Wijck by Sunil Soraya. This research is expected to provide understanding for reader and writer about novel ecranization of Tenggelamnya Kapal Van Der Wijck to the movie Tenggelamnya Kapal Van Der Wijck which includes varying shrinkage, additions and changes. The method used in this research was descriptive method using literature study approach. Sources of data from this research were the script or the novel text of the Tenggelamnya Kapal Van Der Wijck ship and scene film Tenggelamnya Kapal Van Der Wijck. Data collection technigues are done by reading novels, watching movies and taking scene on film. The data analysis technique used a flow model proposed by Miles and Huberman. The results show that there were 82 aspects of sharinkage, 64 aspects of addition, and 38 aspects of varied changes that occurred after the novel ecranization process into the movie.